2015
DOI: 10.1111/1467-6427.12073
|View full text |Cite
|
Sign up to set email alerts
|

Does partners’ differentiation of self predict dyadic adjustment?

Abstract: The present study expands on Bowen’s systemic multigenerational theory to analyse the role of individual trajectories of differentiation of self in perceived dyadic adjustment in a sample of 468 Italian participants. The research also explored which aspects of differentiation of self most strongly predicted dyadic adjustment in the total sample and in male and female subsamples. The various components of differentiation of self (emotional reactivity, emotional cut-off, emotional fusion and I-position) and dyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 26 publications
6
33
1
2
Order By: Relevance
“…Moreover, they show evidence that DoS has important implications for physical and mental well‐being. Our results also support a growing body of literature that confirms the cross‐cultural relevance of BFST (e.g., Ferreira, Fraenkel, Narciso, & Novo, ; Lampis, ; Rodríguez‐González et al., ) and extend these findings by demonstrating that the BFST offers relevance for adults in Spanish cultures. Additional intervention and psychotherapy process research is needed to assess whether and how the therapeutic process might influence levels of differentiation in order to promote client resiliency in the face of anxiety and life stress.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, they show evidence that DoS has important implications for physical and mental well‐being. Our results also support a growing body of literature that confirms the cross‐cultural relevance of BFST (e.g., Ferreira, Fraenkel, Narciso, & Novo, ; Lampis, ; Rodríguez‐González et al., ) and extend these findings by demonstrating that the BFST offers relevance for adults in Spanish cultures. Additional intervention and psychotherapy process research is needed to assess whether and how the therapeutic process might influence levels of differentiation in order to promote client resiliency in the face of anxiety and life stress.…”
Section: Resultssupporting
confidence: 89%
“…They can cope appropriately with stressful situations while maintaining proper functioning of each of these. Prior studies conducted overseas have reported results generally supporting the hypothesis of differentiation of self (e.g., Choi & Murdock, 2017;Jankowski, Hooper, Sandage, & Hannah, 2013;Lampis, 2016).…”
Section: Differentiation Of Self Hypothesissupporting
confidence: 53%
“…Differentiation of self seems to be fundamental to an individual's capacity to achieve intimacy and mutuality in marriage. In recent years, many studies have proposed that differentiation of self is an important predictor of the quality of romantic relationships, and there are many reports that individuals and couples who report good self‐differentiation are more satisfied with their intimate relationships and experience less relational conflict than those who report fusion with others, emotional reactivity, or emotional cut‐off (Anderson & Sabatelli, ; Aryamanesh et al., ; Knauth & Skowron, ; Lampis, ; Lampis, Cataudella, Busonera, & Skowron, ; Mohsenian, Karamlo, & Ganjavi, ; Peleg, ; Rodríguez‐González et al., ; Sabatelli & Bartle‐Haring, ; Skowron, ). These findings also are consistent with research (Gubbins et al., ; Schwartz, Thigpen, & Montgomery, ) trying to connect Bowen's theory self‐differentiation with Gottman's model of marital interactions (Gottman, ; Gottman & DeClaire, ; Gottman & Silver, ) and with research showing that spouses’ differentiation from their birth family was associated with emotional flooding during arguments and marital satisfaction (Gubbins et al., ) and with failure to create a stable sense of self (Schwartz, Thigpen, & Montgomery, ).…”
Section: Differentiation Of Self and Couple Relationshipsmentioning
confidence: 99%
“…The emotional cut‐off style is characterized by feeling anxious about losing one's sense of self and managing this threat to autonomy through physical or emotional avoidance or by creating conflict in one's intimate relationship. People with an emotionally reactive style tend to react to external and internal stressors with irrational and intense emotional arousal (Harrison, ; Lampis, ; Lampis, Busonera, Cataudella, & Skowron, ; Lampis, Cataudella et al., ; Yousefi et al., ). What is not clear is how I‐position, fusion with others, emotional reactivity, and emotional cut‐off affect dyadic adjustment.…”
Section: Differentiation Of Self and Couple Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation